Translation methods of a fansub by Kyuubisubs of episode 74 of the Fairy Tail anime - Bastiko Pradhana (UPT P2M Politeknik Negeri Malang, 2016)
To make foreign films such as Japanese anime accessible to other viewers, subtitling can be used to provide a written translation directly on the picture. But what translation methods would subtitles use, especially those of a fansub? This research examined a particular episode of the Fairy Tail anime using a fansub created by KyuubiSubs. This research also used the theory of translation methods as outlined by Newmark (1981). It was found that individual lines of the subtitling trended toward source-language methods with other methods having different effects. Ultimately the subtitles were judged to have a literal translation method.